Selection Method, Partisanship, and the Administration of Elections. (November 2013) - Burden, Barry C.; Canon, David T.; Lavertu, Stéphane; Mayer, Kenneth R.; Moynihan, Donald P.
The methods used to select public officials affect the preferences they bring to office, the incentives they face while in office, and, ultimately, the policy goals they pursue. We argue that the preferences and actions of local election officials (LEOs) differ depending on whether they are elected or appointed. We test these expectations with a data set that includes the survey responses of 1, 200 Wisconsin LEOs, structured interviews, census data, and returns from the 2008 presidential election. Drawing upon a natural experiment in how officials are selected, we find that, compared to appointed officials, elected officials express greater support for voter access and expressless concern about ballot security and administrative costs. For appointed officials, we find that voter turnout in a municipality is lower when the LEO's self-reported partisanship differs from the partisanship of the electorate but only in cases where the official is a Republican.